Comparative Phase Solubility Analysis of Olanzapine by 24 Optimization Techniques with Different Water-Soluble Carriers - Sundaramoorthi, Revathi; Pavadai, Anitha; Sathappan, Jenifer; Sivakumar, Senthil Rajan (International Journal of Pharmaceutical Investigation, 2025)
Background The solubility of medications significantly affects their absorption and therapeutic effectiveness. Drugs with poor solubility often faces challenges in formulation development leading to low bioavailability and fluctuations in blood concentration. Olanzapine, an atypical antipsychotic drug used in treating schizophrenia, exemplifies this issue with its low water solubility and subsequent low bioavailability. Materials and Methods This study explores the enhancement of olanzapine's solubility through the use of various carriers, including urea, polyethylene glycol 4000, polyvinyl pyrrolidone K-30 and carboxy methyl cellulose. Method: Response surface methodology using 24 optimization technique was employed to evaluate the solubility enhancement potential and optimize the formulation parameters. Regression equations and contour plots were utilized to elucidate the relationship between carriers, carrier ratios and solubility-related parameters such as dissociation constant, complexation efficiency, Gibbs free energy and solubility. Results and Conclusion The findings show that polyvinyl pyrrolidone K-30 has a positive impact on solubility-related parameters as its concentration rises. Polyvinyl pyrrolidone K-30 surmounts other carriers for making potent Olanzapine formulations.
Keywords: Olanzapine; Phase Solubility; Polyvinyl Pyrrolidone K-30; Complexation Efficiency